Law On Notary Engaged Omissions In Deed Minuta Storage Under Law Number 2 Year 2014 Concerning The Position Notary - Iin Kamila; Sri Endah Wahyuningsih; Yudhi Atmaja (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to: 1) To know and analyze the enforcement of the negligence of the notary deed minuta storage based on Law No. 2 of 2014 on the notary office. 2) To know and analyze what are the obstacles and solutions in enforcing the law against the negligence of the notary deed minuta storage based on Law No. 2 of 2014 on the notary office. The data used in this study are primary data, secondary data and data that can support tertiary study, which was then analyzed by descriptive analytical method.Keywords: Law Enforcement, Negligence Penyimpana, Minuta Deed